Every Tuesday - Schaller, Evamaria (Austria : Schaller, Evamaria, 2007)
The setting for the film is a cozy corner in a restaurant. A guest and a waiter are engaged in a dialogue that ends in revealing insanity.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Fiction films